Quality of work life and burnout syndrome in employees in the retail sector of Metropolitan Lima - Garcés Ortiz, Claudia Rozana (2020)
The objective of this research is to know the relationship between quality of work life (QWL) and Burnout syndrome (BOS) in employees in the Retail sector of Metropolitan Lima. The type of research was descriptive correlational and the purpose was not experimental and transectional, in a non-probabilistic and intentional sample of 129 the employee’s collaborations between men and women with a minimum of six months of experience in face to face contact with the client in the sale of Retail products. The results of our observation indicate that there is a significant and negative association between quality of work life and Burnout Syndrome. An analysis of the QWL with the dimensions of the BOS shows us that there is a significant and inverse relationship between quality of work life and overwhelming exhaustion and depersonalization; instead the association with personal development is significant and positive.